Difference between revisions of "99 questions/Solutions/17"

From HaskellWiki
Jump to navigation Jump to search
 
(cleanup)
Line 3: Line 3:
 
Do not use any predefined predicates.
 
Do not use any predefined predicates.
   
Solution using take and drop:
+
Solution using <hask>take</hask> and <hask>drop</hask>:
  +
 
<haskell>
 
<haskell>
 
split xs n = (take n xs, drop n xs)
 
split xs n = (take n xs, drop n xs)
 
</haskell>
 
</haskell>
   
  +
Or even simpler using <hask>splitAt</hask>:
Alternatively, we have the following recursive solution:
 
  +
  +
<haskell>
  +
split = flip splitAt
  +
</haskell>
  +
 
But these should clearly be considered "predefined predicates". Alternatively, we have the following recursive solution:
  +
 
<haskell>
 
<haskell>
 
split :: [a] -> Int -> ([a], [a])
 
split :: [a] -> Int -> ([a], [a])
Line 18: Line 26:
   
 
The same solution as above written more cleanly:
 
The same solution as above written more cleanly:
  +
 
<haskell>
 
<haskell>
 
split :: [a] -> Int -> ([a], [a])
 
split :: [a] -> Int -> ([a], [a])
Line 23: Line 32:
 
split (x:xs) n = let (f,l) = split xs (n-1) in (x : f, l)
 
split (x:xs) n = let (f,l) = split xs (n-1) in (x : f, l)
 
</haskell>
 
</haskell>
 
Note that this function, with the parameters in the other order, exists as <hask>splitAt</hask>.
 

Revision as of 20:13, 15 July 2010

(*) Split a list into two parts; the length of the first part is given.

Do not use any predefined predicates.

Solution using take and drop:

split xs n = (take n xs, drop n xs)

Or even simpler using splitAt:

split = flip splitAt

But these should clearly be considered "predefined predicates". Alternatively, we have the following recursive solution:

split :: [a] -> Int -> ([a], [a])
split []         _             = ([], [])
split l@(x : xs) n | n > 0     = (x : ys, zs)
                   | otherwise = ([], l)
    where (ys,zs) = split xs (n - 1)

The same solution as above written more cleanly:

split :: [a] -> Int -> ([a], [a])
split xs 0 = ([], xs)
split (x:xs) n = let (f,l) = split xs (n-1) in (x : f, l)